2017
DOI: 10.21767/2472-1646.100024
|View full text |Cite
|
Sign up to set email alerts
|

Serological Biomarker Panel (GastroPanel®): A Test for Non-Invasive Diagnosis of Dyspeptic Symptoms and for Comprehensive Detection of Helicobacter pylori Infection

Abstract: The two major risk factors of Gastric Cancer (GC) are Helicobacter pylori (HP) infection and Atrophic Gastritis (AG) It is currently possible to diagnose HP-infection and AG by using serological testing with a panel of biomarkers (GastroPanel ® , Biohit Oyj, Finland): Pepsinogen I (PGI), Pepsinogen II (PGII), and HP-antibodies. In this review, an introduction is made to the GastroPanel ® test as the first non-invasive diagnostic tool for: i) Dyspeptic symptoms, ii) Screening of asymptomatic subjects for the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(43 citation statements)
references
References 66 publications
(130 reference statements)
0
40
0
3
Order By: Relevance
“…In general, gastric bacterial overgrowth even with bacterial and fungal bezoars is a constant phenomenon in an acid-free stomach (28). In the late 1990s, it was demonstrated that the number of microbes in gastric mucosa is comparable to that of gastric juice (35), and these non-Hp bacteria are also embedded in the mucus and even in close contact with the gastric epithelium, similarly to Hp (36)(37)(38).…”
Section: The Ubtmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, gastric bacterial overgrowth even with bacterial and fungal bezoars is a constant phenomenon in an acid-free stomach (28). In the late 1990s, it was demonstrated that the number of microbes in gastric mucosa is comparable to that of gastric juice (35), and these non-Hp bacteria are also embedded in the mucus and even in close contact with the gastric epithelium, similarly to Hp (36)(37)(38).…”
Section: The Ubtmentioning
confidence: 99%
“…GastroPanel ® was introduced in a series of recent communications (37,38,(43)(44)(45). The test is composed of enzyme-linked immunosorbent assays (ELISA) of three biomarkers: pepsinogen I (PGI), pepsinogen II (PGII) and gastrin-17 (G-17), combined with an ELISA assay of Hp (IgG) antibodies, all being measured from the same serum/plasma sample (43)(44)(45).…”
Section: The Shortcomings Of Ubt and Sat Can Be Avoided By Use Of A Pmentioning
confidence: 99%
See 2 more Smart Citations
“…Iron deficiency anemia, which is often present in patients with AIG, should be identified by levels of hemoglobin, mean corpuscular volume (MCV), serum iron, ferritin, total iron-binding capacity (TIBS) and serum transferrin receptor (TfR). In patients with suspected carcinoid tumor transformation the measurement of chromogranin A, which is secreted by the ECL cells, can be useful, although it shows low specificity (23%) and false-positive results in patients with inflammatory bowel disease, renal insufficiency and other conditions [4, 23, [35][36][37][38][39][40][41][42][43][44][45].…”
Section: Diagnostic Approach 41 Serological Testsmentioning
confidence: 99%